Le petit-fils de Turgut Reis vivant en Tunisie, est fier de ses ancêtres - Turan, Mehmet Akif (Anadolu Ajansi, 2024)
Keywords: Ottomans – Djerba

Une puissance navale en méditerranée - Poumarède, Géraud (Historia - Spécial, 2020)
À partir de la seconde moitié du XVe siècle, l'Empire ottoman se dote d'une flotte puissante. Elle lui permet d'assurer la sécurité des routes maritimes qui convergent vers ...
Keywords: Ottomans – Djerba

Espionage in the 16th Century Mediterranean_ Secret Diplomacy, Mediterranean Go-Betweens and the Ottoman Habsburg Rivalry - Gürkan, Emrah Safa (Georgetown University, 2012)
Keywords: Ottomans – Djerba

The efficacy of Ottoman counter-intelligence in the 16th century - Gürkan, Emrah Safa (Acta Orientalia Academiae Scientiarum Hungaricae, 2012)
This article examines the Ottoman counter-intelligence mechanism and the extent to which it succeeded in preventing enemy intelligence. In the 16th century, the length and the scope of both Ottoman – Habsburg and the Ottoman Safavid Rivalry convinced the Ottomans to establish an intelligence network that gathered information in a large geography. Nevertheless, in the war of information between the Ottomans and their rivals, the success of Ottoman information-gathering was intertwined with the efficiency of Ottoman counter-intelligence. In order to gain an advantage in “politics of information”, the Ottoman secret diplomacy successfully refused its enemies a comfort which it sought for itself: access to information about the adversary.
Keywords: Ottomans – Djerba

Lair of Corsairs on the Djerba Island in the First Half of the Sixteenth Century - Jaguś, Patryk (Prace Naukowe Uniwersytetu Humanistyczno-Przyrodniczego im. Jana Długosza w Częstochowie. Zeszyty Historyczne, 2018)
This article concerns the activities of the brothers Oruk and Hayreddin Barbarossa during they residence on the North African island of Djerba. Before the Red Beard brothers occupied the kingdom of Algiers and made themselves his kings, they gave themselves under the protection of the ruler of Tunis. He offered them the island of Djerba, where the corsairs made their first base. From there, they carried out expeditions to the entire central and western Mediterranean.
Leże korsarzy na wyspie Dżerbie w pierwszej połowie XVI wieku
Keywords: Ottomans – Djerba